THE The Physicochemical Characteristics of Cilembu Sweet Potato Flour Made from Different Process - Suprijon, Maria Matoetina; Widyastuti, Theresia Endang Widoeri; Widjajaseputra, Anna Ingani (Metamorfosa: Journal of Biological Sciences, 2023)
East Java is one of the centres of Cilembu orange sweet potato which has the highest beta-carotene content. Fresh sweet potato has a limited shelf life so it is processed into flour but it causes colour degradation of sweet potato flour. Therefore, it is necessary to investigate the use of drying temperature and orange sweet potato shaped which can still maintain the physicochemical properties, as well as have the functional properties needed in processing of the next product. The Cilembu orange sweet potato samples used in this study were generally shaped like a spindle with an average length of 17.27+2.64 cm, the diameter of the top 4.28+0.72 cm, middle 7.04+0.69 cm and bottom 5.08+1.12 cm. Drying using a cabinet drier at 50?C resulted in the yield of flour from the sliced ??treatment was 16.78% and grated flour was 6.34%. Slices and grated before drying affected the colour, gelatinization profile, and viscosity of the flour samples. The water absorption of the flours was 1.90+0.05 ml/g. The flours colour looked paler than the fresh, but the L* value of grated flour was higher than sliced flour. The values ??of a* and b* decreased significantly even though they were still positive, which means they were still orange. Based on the values ??of L*, a*, b*, the sliced ??treatment was able to maintain the colour of the flour samples better (more orange) than the grated. The grated flour had very varied starch granule sizes. This affects the unstable gelatinization and viscosity profile.